2021
DOI: 10.1186/s41610-021-00193-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of mean temperature and 9 collected butterfly species’ wingspan as the response of global warming

Abstract: Background Organism body size is a basic characteristic in ecology; it is related to temperature according to temperature-size rule. Butterflies are affected in various aspects by climate change because they are sensitive to temperature. Therefore, this study was conducted to understand the effect of an increase in temperature due to global warming on the wing of butterflies. Results A total of 671 butterflies belonging to 9 species were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
7
2
Order By: Relevance
“…Interestingly, our wingspan results were contrary to the 'temperature-size rule' [38], which suggest that adults of ectotherms raised at higher temperatures are smaller than their counterparts raised at cooler temperatures [37,38]. This rule is far from absolute, with several studies showing contradictory findings [39,40]. Indeed, the likelihood of temperature having a positive, negative or neutral impact on wingspan can be species-specific [39] or dependent on the developmental stage at which the temperature increase occurs [40].…”
Section: Temperature Effects On Phenological and Morphological Attrib...contrasting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, our wingspan results were contrary to the 'temperature-size rule' [38], which suggest that adults of ectotherms raised at higher temperatures are smaller than their counterparts raised at cooler temperatures [37,38]. This rule is far from absolute, with several studies showing contradictory findings [39,40]. Indeed, the likelihood of temperature having a positive, negative or neutral impact on wingspan can be species-specific [39] or dependent on the developmental stage at which the temperature increase occurs [40].…”
Section: Temperature Effects On Phenological and Morphological Attrib...contrasting
confidence: 84%
“…This rule is far from absolute, with several studies showing contradictory findings [39,40]. Indeed, the likelihood of temperature having a positive, negative or neutral impact on wingspan can be species-specific [39] or dependent on the developmental stage at which the temperature increase occurs [40]. For instance, Wilson et al [40] found that adults from different families of butterflies that were exposed to higher temperatures at late larval stages, as per our experiment, had substantially larger wingspans than adults exposed at earlier larval or pupal stages.…”
Section: Temperature Effects On Phenological and Morphological Attrib...mentioning
confidence: 99%
“…This suggests that, at least in some insect groups, phylogenetic relationships are also an important predictor of the direction and magnitude of temperature‐size responses. Butterflies often increase in adult size with increasing temperature (MacLean et al, 2016; Na et al, 2021; but see Bowden et al, 2015) and analysis of four UK butterfly species found that the strongest prediction of adult size was temperature during the late larval stage (Fenberg et al, 2016; Wilson et al, 2019). But in order to determine if these are general responses, more species and specimens need to be analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Such a reduction in size appears to be most pronounced among aquatic species, which is likely due to oxygen limitation in warmer waters (Forster et al, 2012). On the other hand, many terrestrial species exhibit variable temperature‐size responses (Horne et al, 2015; Na et al, 2021; Tseng et al, 2018; Wonglersak et al, 2020). This is especially true for insects, which, due to their complex and diverse life cycles, can lead to a variety of temperature‐size responses.…”
Section: Introductionmentioning
confidence: 99%
“…Forewing length of Colias meadii meadii increased as environments warmed in the Rocky Mountains, where longer growing seasons may promote greater larval food availability (MacLean et al 2016). An analysis of butterfly species in Seoul and Mokpo, South Korea, also found increases in wing length over time (Na et al 2021). Increasing body sizes have also been reported to accompany climate warming in bumblebees (Gérard et al 2020).…”
Section: Introductionmentioning
confidence: 97%